The Effect of Human Engineering on Occupational Security and Safety in Jordanian Industrial Companies: A Case Study Manaseer Oil & Gas Company - Alserhan, Hayel; Al-Adamat , Abdullah; Al-Quran, Ali (The Arab Journal of Administration, 2021)
This study aims to identify the impact of human engineering (and all of its dimensions: work organizing, position and movement, environmental factors, information and operations) on occupational safety and security in Jordanian industrial companies, Manaseer Oil & Gas Company as a case study. The sample of the study consisted of (188) workers from Manaseer Oil & Gas Company. The results of the study showed that the level of employees’ perceptions towards applying human the standards of engineering in the company was average, and the level of their perceptions towards achieving the standards of occupational safety and security in the company was also average. Furthermore, the results of the study indicated that there is a statistically significant effect of applying human engineering standards on occupational safety and security in Manaseer Company. More specifically, there was a statistically significant effect for the position and movement dimension, the environmental factors dimension, and the information and operations dimension on the occupational safety and security in the company. However, there was no statistically significant effect for of the work organization dimension on occupational safety and security. The study recommended the necessity of working on creating a specialized administrative unit in each station under the name of the Human Engineering Unit to manage and supervise the safety of workers at the station and the safety of the station itself, and to increase training programs for human engineering for all company employees to increase their knowledge and familiarity with issues of occupational safety and security.